Study of the Effect of Domestic Wastewater from Jalan Lele Residents of Palangka Raya City on the Acidity and Alkalinity Levels of the Receiving Water Body: Studi Pengaruh Air Limbah Domestik Penduduk Jalan Lele Kota Palangka Raya terhadap Kadar Asiditas dan Alkalinitas Badan Air Penerima - Manurung, Tety; Natalia, Nasa; Suma, Joy Angel Aria; Purba, Abed Nego; Naiya, Naiya; Hulu, Dominique F.S.; Rosmainar, Lilis; Hermayantiningsih, Dwi (Jurnal Jejaring Matematika dan Sains, 2023)
This research aims to determine the impact of domestik waste water disposal produced by residents living on Jalan Lele, Palangka Raya City, on the value of acidity and alkalinity levels in the receiving water body. The acidity level obtained was 24.098 mg/L and the alkalinity level was 254.410 mg/L. The acidity levels not comply to the Government Regulation Number 20 of 1990 levels and Government Regulation Number 82 of 2001 for standart water quality type B. Similarly for alkalinity levels doesn’t comply to World Heal Organization Regulation 2011 for irrigation water. Based on the results ​​of high levels of acidity and alkalinity in receiving water bodies, it encourages further research to be carried out for monitoring and handling domestik waste in residential areas in the city of Palangka Raya.